Evaluation of an intervention programme addressing ability to perform activities of daily living among persons with chronic conditions: study protocol for a feasibility trial (ABLE). Issue 5 (20th May 2018) - Guidetti, Susanne; Nielsen, Kristina Tomra; von Bülow, Cecilie; Pilegaard, Marc Sampedro; Klokker, Louise; Wæhrens, Eva Ejlersen
Abstract : Introduction: The number of persons living with a chronic condition is increasing worldwide. Conditions are considered chronic when lasting 1 year or more and requiring ongoing medical attention and/or limiting activities of daily living (ADL). Besides medical treatment, physical exercise to improve body functions is recommended and prescribed. However, improvements in body functions do not necessarily improve ability to perform ADL. Thus, it is necessary to develop interventions aiming directly at enhancing ADL ability. As a part of the research programme 'A Better Everyday Life', the first version of the ABLE intervention programme was developed. Methods and analysis: This feasibility study examine the perceived value and acceptability of the ABLE programme by evaluating the fidelity, reach, dose and potential outcomes using a pretest and post-test design involving 30 persons living with chronic conditions. Qualitative interviews among occupational therapists delivering and participants receiving the ABLE programme will be conducted to explore aspects affecting the intervention. Ethics and dissemination: The results will form the base for refinement of the ABLE programme and planning of a large-scale randomised controlled trial investigating the effect of the programme on self-reported and observed ADL ability. Dissemination will include peer-reviewed publications and presentations at national and international conferences. Protocol version: 7 November 2017: v ersion 1.0. 19 February 2018: v ersion 2.0. Trial registration number: NCT03335709 ; Pre-results.